Classical tradition and transgression in Áyax by Reinaldo Montero (Iter, 2022)
Attic tragedy deals with myths, pa rticu la rly th e ones in the Theban and TrojanCycles, in order to make one reflect on highly topical subjects in Greek society atthat time, and on troubles affecting man in general. Different expressions of politicalpower are present in Aeschylus’ oeuvre, an d despite claims always made thatSophocles shifts attention to the individual a n d family, works like Antigone and evenOedipus have made a great impact on rethinking tyrannical power later. However,there are only a very few modern works being based on Sophocles’Ajax, and thecritics usually study the tragedy, focusing on other aspects. That is why it is verysignificant that the Cuban playwright Reinaldo Montero -whose version of Medeamade him famous in 1996, after winning the Italo Calvino Prize, and who wrote hisown version of Antigone in 2009- revisited the Trojan myth and Sophocles’tragedy inorder to write his Ajax in 2013 that was just premiered in 2016 by the name of Ajaxand Cassandra . By means of figures established by that important event in Greekmythology, and by Attic tragedy, Montero brings to light a highly topical subjectregarding secrets had and wiles used by power holders, by stressing the role playedby poetry in the past and by mass media nowadays, and shows how today’s culturehas received classical antiquity.
Keywords: Attic Tragedy - Power - C u b an Theater - Classical Tradition - Transgression - Ajax - Reinaldo Montero